On the Asymptotic Stability Behaviours of Solutions of Non-linear Differential Equations with Multiple Variable Advanced Arguments - Biçer, Emel; Tunç, Cemil (Journal of Applied Nonlinear Dynamics, 2026)
We pay our attention to a non-linear differential equation of first order with multiple two variable advanced arguments. We find sufficient conditions satisfying the convergence (C) and exponential convergence (EC) of solutions of the considered non-linear advanced differential equation (NADE) by contraction mapping principle (CMP). The obtained results improve and extend the results can be found in the relevant literature from a case of linear advanced differential equation (LADE) of first order to a case of (NADE) of first order with multiple two variable advanced arguments. We give examples for illustrations by applying MATLAB-Simulink. It is also clearly shown the behaviors of the orbits for the special cases of the considered (NADE).